Evolutionary conditions of happiness - Höffken, Ole (Journal of happiness studies, 2025)
Subject of this review are evolutionary conditions for affective factors relevant to happiness, with ‘happiness’ understood as a positive psychological state or condition, and ‘evolution’ denoting both natural and cultural selection processes in human history. A widely shared assumption is that a central aspect of happiness is a favorable balance between positive and negative affective states. This motivates the question: with which circumstances of life such a balance is predictably correlated? An answer complementing ‘proximate’-functional approaches may be given via describing human evolutionary developments and their relevance to affective states, especially under modern conditions of life. This approach has been characterized recently as ‘Positive Evolutionary Psychology’. The paper reviews this developing field of research. It is considered how the factors of natural and cultural human evolution can explain and be correlated with the occurrence of positive or negative affect. From an evolutionary perspective, affective states appear as part of a biological motivational system, while humans as a cultural species seek a favorable balance of positive and negative affect as an end in itself. But realizing happiness is challenging, especially under conditions of modern societies, which have created an environment encompassing various ‘evolutionary mismatches’ in comparison to ancestral conditions of life. Concerns with status, wealth, and consumption have strong biological underpinnings, while also being ‘supernormally’ stimulated in modern societies. This leads to cognitive overload, addictive dynamics, and estrangement from similarly evolved needs for belonging and cooperation. These considerations suggest that broader dissemination of knowledge about evolutionary influences on human behavior and happiness may encourage a conscious distancing from excessive status and pleasure seeking.
Gesehen am 14.01.2026